Effects of potassium deficiency on renal function in the dog - Abbrecht, Peter H. (1969)
Serial determinations of the renal clearance for inulin and para-aminohippuric acid (PAH), maximum renal tubular reabsorptive rate for glucose, maximum urinary concentrating ability, total exchangeable potassium, extracellular volume, and plasma sodium and potassium concentrations were done in seven dogs before and after dietary potassium depletion. The same measurements were also made in two of the dogs during potassium repletion. Inulin and PAH clearances and transport maxima for glucose decreased progressively during depletion. These changes correlated well with both the duration of depletion and the extent of depletion as measured by total exchangeable potassium. Decreases in inulin and PAH clearance closely paralleled each other, suggesting that there might be a renal hemodynamic basis for both effects. The decreases in transport maxima for glucose were greater than those for inulin or PAH clearance, indicating the presence of a defect in the cellular transport mechanism for glucose. In the dogs that were repleted, renal function gradually returned to the predepletion state. No significant changes were found in extracellular volume or plasma sodium concentration during depletion. Renal concentrating ability decreased only moderately during depletion, with the decrease correlating better with plasma potassium concentration than with total exchangeable potassium. This finding contrasts with the marked decrease in concentrating ability and the severe polydipsia and polyuria found in animals depleted of potassium with the aid of corticosteroids. The results of the present study emphasize the importance of considering species differences and the method of producing depletion in interpreting studies of the effects of hypokalemia on renal function.